Consumer Profiles and Drink Menus Made from Medicinal Plants at the Jamu Cafe in Depok Sleman District, Yogyakarta - Hartini, Yustina Sri; Setiawati, Agustina; Dwiatmaka, Yohanes (Jurnal Jamu Indonesia, 2024)
The use of medicinal plants as ingredients in making drinks in cafes is increasing along with the number of cafes. Herbal café makes a unique menu using medicinal plants in drink recipes to produce a distinctive taste, color, and aroma. This research aims to identify visitor profiles and drink menus made from medicinal plants and explore the understanding of visitors and cafe owners regarding the benefits of medicinal plants added to drinks. The research data collection technique uses a questionnaire equipped with an interview sheet. The questionnaires and interview sheets used have been tested for language comprehension and validity. The research was conducted at 272 cafes in Depok District, Sleman Regency, Special Region of Yogyakarta. The sample was determined using purposive sampling, data was collected after obtaining ethical clearance approval from the Health Research Ethics Committee Team. Data was obtained through filling out surveys by visitors and cafe owners, complemented by interviews with cafe owners. Data was collected three times: August, September, and October 2023. Data analysis was carried out descriptively and qualitatively. Most herbal cafe visitors (70%) are aged between 21–30 years with the majority of professions (44%) being students. The source of information about herbal cafe menus was mostly obtained (56%) from friends or family, and the frequency of visits to cafes was mostly (82%) between 1–5 times per month. More than 98% of visitors stated the benefits of medicinal plants in the drink menu, namely as a refresher or body warmer. There are 14 types of medicinal plants used as ingredients in the herbal cafe's drink menu, with a total monthly requirement for all medicinal plants of 545.1 kilograms; ginger ranks among the highest requirements. Recipe information for the menu was obtained from the family, the Ministry of Health Republic Indonesia website, and the herbal cafe owner made the recipe independently.